Preemptive scheduling with position costs - Sourd, Francis (Algorithmic Operations Research)

(untitled) (Preeminent Academic Facets Inc., 2006)
This paper is devoted to basic scheduling problems in which the scheduling cost of a job is not a function of its completion time. Instead, the cost is derived from the integration of a cost function over the time intervals on which the job is processed. This criterion is specially meaningful when job preemption is allowed. Polynomial algorithms are presented to solve some special cases including a one-machine problem with a common due date and a two-machine problem with linear nondecreasing cost functions.